A comprehensive review of the impacts of climate change on agriculture in Thailand - Muhammad Waqas; Adila Naseem; Usa Wannasingha Humphries; Phyo Thandar Hlaing; Muhammad Shoaib; Sarfraz Hashim (Farming System)
The agricultural sector is vulnerable to climate change (CC). Various climate-related extremes, such as droughts, heat waves, unpredictable rainfall patterns, storms, floods, and an increase in insect pests, have adversely affected farmers' livelihoods. Climate forecasts indicate a significant increase in temperatures and more inconsistent, extreme rainfall, obfuscating the prediction of extreme weather events. The IPCC projects that by the end of the 21st century, temperatures in Thailand will rise by 0.95 ​°C–3.23 ​°C. This study aims to review the current understanding of CC's impact on the agricultural sector and evaluate the adaptation measures being employed in Thailand. Farmers have begun adopting adaptive measures such as alternative farming techniques, crop diversification, and water management strategies to mitigate climate risks and maintain productivity. However, limited resources, knowledge gaps, and insufficient government support hinder widespread adoption. Targeted interventions and policy support are essential for enhancing adaptive capacity and resilience. The impacts on crop water requirements and livelihoods reveal vulnerabilities due to extreme weather events. Rain-fed agriculture faces significant yield declines and reduced crop water productivity, exacerbating economic impacts on rural households and leading to food insecurity and financial instability. Effective adaptation requires enhanced water management, sustainable practices, and improved institutional support. Community engagement and participatory approaches are vital for building resilience against CC impacts. Comprehensive, region-specific, and long-term studies are crucial for developing robust adaptive strategies.